State of the Art Biocompatible Gold Nanoparticles for Cancer Theragnosis - Moon Sung Kang; So Yun Lee; Ki Su Kim; Dong-Wook Han (MDPI AG, 2020)
Research on cancer theragnosis with gold nanoparticles (AuNPs) has rapidly increased, as AuNPs have many useful characteristics for various biomedical applications, such as biocompatibility, tunable optical properties, enhanced permeability and retention (EPR), localized surface plasmon resonance (LSPR), photothermal properties, and surface enhanced Raman scattering (SERS). AuNPs have been widely utilized in cancer theragnosis, including phototherapy and photoimaging, owing to their enhanced solubility, stability, biofunctionality, cancer targetability, and biocompatibility. In this review, specific characteristics and recent modifications of AuNPs over the past decade are discussed, as well as their application in cancer theragnostics and future perspectives. In the future, AuNP-based cancer theragnosis is expected to facilitate the development of innovative and novel strategies for cancer therapy.